STRATEGI DALAM MENINGKATKAN KEPATUHAN MASYARAKAT TERHADAP PROTOKOL KESEHATAN DI MASA PANDEMI COVID-19 - Sa’adah, Qheniyyatus; Nugroho, Setiyo Adi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
Corona virus disease (covid-19) is an infectious disease. Prevention of covid is by complying with health protocols. Knowledge is one of the factors of non-compliance, knowledge can be increased through education. The research method we use here is literature review using electronic databases through international and national journals such as google scientist, science direct, pro-quest, jstor with the keyword